Exosomes and Nanoengineering: A Match Made for Precision Therapeutics. Issue 18 (18th September 2019) - Tran, Phuong H. L.; Xiang, Dongxi; Tran, Thao T. D.; Yin, Wang; Zhang, Yumei; Kong, Lingxue; Chen, Kuisheng; Sun, Miaomiao; Li, Yong; Hou, Yingchun; Zhu, Yimin; Duan, Wei
Abstract: Targeted exosomal delivery systems for precision nanomedicine attract wide interest across areas of molecular cell biology, pharmaceutical sciences, and nanoengineering. Exosomes are naturally derived 50–150 nm nanovesicles that play important roles in cell‐to‐cell and/or cell‐to‐tissue communications and cross‐species communication. Exosomes are also a promising class of novel drug delivery vehicles owing to their ability to shield their payload from chemical and enzymatic degradations as well as to evade recognition by and subsequent removal by the immune system. Combined with a new class of affinity ligands known as aptamers or chemical antibodies, molecularly targeted exosomes are poised to become the next generation of smartly engineered nanovesicles for precision medicine. Here, recent advances in targeted exosomal delivery systems engineered by aptamer for future strategies to promote human health using this class of human‐derived nanovesicles are summarized. Abstract : Recent advances in research and development of aptamer‐guided exosomes as a new nanoengineering strategy to achieve targeted drug delivery using bio‐nanoparticles highlight a promising next generation of targeted drug delivery systems. Cross‐fertilization between areas of exosomes and aptamers in both preclinical translational studies predicts a bright future for aptamer‐guided exosomal delivery in precision nanomedicine.